Comparison of the Effectiveness of Parent-Centered Meta-Emotional Training and Family-Centered Play Therapy in Reducing Aggression in Preschool Children - Zahra Mohammadzadeh; Molouk Khademi Ashkzari; Khadijeh Abolmaali Alhosseini (پژوهش‌های کاربردی روانشناختی)
Preschool children's hostility in comparison to family-centered play therapy and parent-centered meta-emotional training. The control group underwent a pre-test, post-test, and follow-up as part of the semi-experimental design. The statistical population consisted of 45 preschool children from Tehran in 2021-2022, who were selected through targeted sampling. The parents of the first and second experimental groups were treated with parent-centered meta-emotional training and family-centered play therapy, respectively. The research tool was aggression questionnaire of preschool children (APC). The data were analyzed using SPSS 22 software for repeated measure analysis of variance. In the post-test and follow-up phase, both parent-centered meta-emotional training and family-centered play therapy significantly reduced the aggression of children (P>0.001) However, there was no significant difference in the effectiveness of the two groups (P<0.05). In parent-centered meta-emotional training, the child’s capacity to express his emotions was enhanced, thereby reducing the likelihood of aggressive behavior. This was achieved by assisting parents in emphasizing the child's emotions and feelings and adopting a receptive perspective toward them. In the family-centered approach, the child’s more adaptive behaviors were significantly altered, and the family’s understanding of how to interact with the child was further enhanced through the use of the game. This allowed the child to express his desires without being compelled to demonstrate aggression. No funding has been allocated to this investigation.